Accountability in Education in British Columbia - Hodgkinson, Douglas (Canadian Journal of Education/Revue canadienne de l’éducation, 1995)
Accountability in education in British Columbia has seven elements: reports, large-scale assessments of student achievement, program evaluation, indicator programs, school accreditation, reference sets, and financial audits. These elements are tied to the goals of education and the attributes of the public school system. This article describes elements that have recently been established or modified. La responsabilité en éducation en Colombie-Britannique comprend sept facettes: les rap- ports, l’évaluation à grande échelle des résultats scolaires, l’évaluation des programmes, les systèmes d’indicateurs, l’agrément des écoles, les ensembles de référence et les vérifications financières. Ces éléments sont reliés aux buts de l’éducation et aux caracté- ristiques du système public d’éducation. Cet article décrit les éléments qui ont été récem- ment mis en place ou modifiés.